Effective and Verifiable Measures Which Would Facilitate the Establishment of a Nuclear-Weapon-Free Zone in the Middle East - Bureau des affaires du désarmement des Nations Unies (United Nations, 1992)
The establishment of a nuclear-weapon-free zone is not a new idea. Two such zones exist in Latin America and the Caribbean and in the South Pacific. This publication discusses a number of steps and measures that could ease the process leading to the establishment of such a zone in the Middle East - an area that can still be termed politically unsettled and militarily volatile. Most of the measures proposed could have a positive effect on the prospects of the region.